Rice Varietal Improvement and International Exchange of Rice Germplasm - Robert E. Evenson (Yale University, Economic Growth Center, 1997)
Rice is the most important food grain in developing countries. Rapid population growth in developing countries during the 1950s and 1960s presented a massive challenge to rice producers. Rice production would have to be expanded at historically unprecedented rates to maintain per capita rice consumption levels. That challenge was met. Rice production expanded more rapidly than population. The challenge was met primarily by increased yields per hectare of land. This paper documents the role of varietal improvement and of genetic resources in achieving yield improvement. It shows that varietal improvement was international in character with the International Rice Research Institute in the Philippines playing the leading role. More than 100 national rice breeding programs contributed to the pool of approximately 2,000 rice varieties constituting the 'green revolution' in rice. Access to and the international exchange of genetic resources in the form of farmer selected 'landraces' was vital. More than ninety percent of the green revolution rice varieties were developed from genetic resorces originating in more than one country.
Keywords: 330; Rice Production; Genetic Resource Evaluation; Rice Productivity; Reisanbau; Gentechnik; Entwicklungsländer